Lithography‐Free Microfabrication of Electrode Arrays with 2 μm Electrode Gaps Using Topographic Templates. Issue 9 (5th September 2014) - Wu, Haosheng; Menon, Monisha; Zhu, Congcong; Balasubramanian, Aditya; Bettinger, Christopher J.
<x xml:space="preserve">Abstract</x> Lithographic‐free and simple fabrication methods for sub‐10 μm electrode arrays are essential for many cost‐effective organic electronic devices. Here we report a non‐lithographic fabrication of electrode arrays with channel lengths as small as 2 μm based on spontaneous wrinkle feature formation and transfer printing. We utilize these structures as electrode arrays in solution‐processable organic thin film transistors. This laboratory‐scale lithography‐free technique may permit rapid electrical characterization of many novel organic semiconducting materials and structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>